2018
DOI: 10.1186/s13018-018-0814-1
|View full text |Cite
|
Sign up to set email alerts
|

Greater rate of cephalic screw mobilisation following proximal femoral nailing in hip fractures with a tip–apex distance (TAD) and a calcar referenced TAD greater than 25 mm

Abstract: BackgroundTo ascertain whether the tip–apex distance (TAD), calcar referenced TAD (CalTAD), and the sum of both (TADcalTAD) are predictive measurements of mobilisation of the cephalic screw in patients with trochanteric hip fractures.MethodsBetween 2014 and 2015, 68 patients (mean age 86 years, 45 females, 23 males) with a trochanteric hip fracture underwent intramedullary nailing. The TAD and CalTAD were measured, and for each parameter, we calculated sensitivity, specificity, positive predictive value (PPV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…This is in accordance with the recently published algorithm for the treatment of per-/intertrochanteric fractures of the hip [19]. The importance of tip apex distance in proximal femoral fractures undergoing nailing has been addressed recently [46]. We acknowledge the limitation due to the fact that we did not measure the tip apex distance related to the fact that a useful tip apex distance does not exist for reconstruction nails.…”
Section: Discussionsupporting
confidence: 84%
“…This is in accordance with the recently published algorithm for the treatment of per-/intertrochanteric fractures of the hip [19]. The importance of tip apex distance in proximal femoral fractures undergoing nailing has been addressed recently [46]. We acknowledge the limitation due to the fact that we did not measure the tip apex distance related to the fact that a useful tip apex distance does not exist for reconstruction nails.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with these findings, a retrospective study of 101 patients in 2018 reported that implant-related complications of PFNA for intertrochanteric fractures treatment were as high as 15.84%, of which 7 were cut out (6.93%), and 2 were secondary varus displacements (1.98%), while TAD > 25 mm and malposition of the spiral blade in the femoral head were found to be important risk factors for secondary varus displacement and screw cutout of the fracture [ 30 , 31 ]. Moreover, a study involving 68 patients with trochanteric fractures using the proximal femoral nailing system showed that there were 36 patients with postoperative TAD < 25 mm, no screw displacement occurred, while the remaining 32 had TAD > 25 mm, and 7 had screw displacement (21.8%); it is worth noting that a total of 15 patients used InterTAN, and only one had a screw mobilization, while 6 (11.3%) receiving Zimmer Natural nail experienced screw mobilization [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For both implants, the migration of the femoral head into varus and retroversion, and the subsequent cut-out of the lag screw/blade, is the most common mechanical complication and are described between 0–7% [10,11,12]. The compromised bone quality in the head and neck of the femur in the typical geriatric patient with osteoporotic bone changes requires an exact positioning of the head screw in the center-center or low-center position and, preferably, a small tip-apex distance (TAD) [13,14]. Additionally, in relation to patient-related characteristics and the positioning of the lag screws, the design of the implants must be taken into account.…”
Section: Introductionmentioning
confidence: 99%